A biomineralized light-guiding structure in the porous calcitic skeleton of the sea star Protoreaster nodosus - Liuni Chen; Hannah Feldstein; Zian Jia; Chenhao Hu; Hongshun Chen; Yang Geng; Emily M. Peterman; Carla Slebodnick; Daniel I. Speiser; Daniel Baum; Mathias Kolle; Ling Li (Proceedings of the National Academy of Sciences, 2026)
Biomineralized structures produced by living organisms are widely recognized for their exceptional mechanical performance, yet their potential optical roles are relatively less explored. Here, we demonstrate that within the calcitic ossicle-based skeleton of the sea star Protoreaster nodosus , where each ossicle represents a discrete skeletal element, one specialized ossicle, known as the terminal plate, contains a radially arranged array of light-guiding structures (LGSs). These LGSs exhibit an elongated, cone-like geometry (~250 μm in length) and are embedded within the porous stereom, a characteristic meshwork architecture of echinoderms analogous to open-cell cellular solids and composed of magnesium-containing single-crystalline calcite. Optical experiments demonstrate that, unlike other skeletal elements, the terminal plate can transmit and focus light into an internal cavity via the LGS array. Combined optical analyses using ray-tracing and finite-difference time-domain simulations reveal that each LGS transmits ca . 70% of incident light at normal incidence and concentrates it up to 2.8-fold at its exiting surface. Furthermore, when acting collectively as the LGS array within the terminal plate, the LGSs capture light over a broad field of view (~120°), resulting in an integrated transmitted intensity that is sixfold to eightfold greater than the incoming intensity perceived by a single LGS. Although the biological function of this optical capability remains uncertain, this natural porous structure demonstrates that cellular solids can integrate efficient light-guiding behavior while enhancing mechanical properties (i.e., threefold increase in stiffness compared with random stereom), offering design insights for lightweight, multifunctional structures.